Application of Suprafascially Harvested Anterolateral Thigh Perforator Flap for the Reconstruction of Oral and Maxillofacial Defects. Issue 7 (October 2020) - Zhang, Shanshan; Li, Panchun; Liu, Chang; Wu, Hanjiang; Gong, Zhaojian
Abstract : Purpose: The aim of this study was to evaluate the feasibility and efficacy of the suprafascially elevated anterolateral thigh (ALT) perforator flap for reconstructing oral and maxillofacial defects. Patients and Methods: The authors analyzed a retrospective case series of 15 patients who underwent reconstruction of oral and maxillofacial defects with the suprafascially raised ALT perforator flap from June 2015 through January 2017 at the Second Xiangya Hospital. The flap harvest and the methods for defect reconstruction are described, and the reconstructive efficacy is reported. Results: Of the 15 patients, 12 were men, and 3 were women, with an average age of 49.5 years. Postoperatively, all flaps survived completely, without vascular compromise or major wound complications. All patients were followed for approximately 1 to 37 months, and they were satisfied with the esthetic and functional results of the recipient- and donor- sites after the reconstruction. Conclusions: Because of the reduced donor-site complications, satisfactory esthetic and functional results, and high success rate of flap transplantation, the use of suprafascially harvested ALT perforator flap is a good choice for the reconstruction of oral and maxillofacial defects, in cases in which the fascia lata is not needed. Abstract : Supplemental Digital Content is available in the text